(5x-2w)(8x-5w)=

Simple and best practice solution for (5x-2w)(8x-5w)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-2w)(8x-5w)= equation:


Simplifying
(5x + -2w)(8x + -5w) = 0

Reorder the terms:
(-2w + 5x)(8x + -5w) = 0

Reorder the terms:
(-2w + 5x)(-5w + 8x) = 0

Multiply (-2w + 5x) * (-5w + 8x)
(-2w * (-5w + 8x) + 5x * (-5w + 8x)) = 0
((-5w * -2w + 8x * -2w) + 5x * (-5w + 8x)) = 0

Reorder the terms:
((-16wx + 10w2) + 5x * (-5w + 8x)) = 0
((-16wx + 10w2) + 5x * (-5w + 8x)) = 0
(-16wx + 10w2 + (-5w * 5x + 8x * 5x)) = 0
(-16wx + 10w2 + (-25wx + 40x2)) = 0

Reorder the terms:
(-16wx + -25wx + 10w2 + 40x2) = 0

Combine like terms: -16wx + -25wx = -41wx
(-41wx + 10w2 + 40x2) = 0

Solving
-41wx + 10w2 + 40x2 = 0

Solving for variable 'w'.

Factor a trinomial.
(2w + -5x)(5w + -8x) = 0

Subproblem 1

Set the factor '(2w + -5x)' equal to zero and attempt to solve: Simplifying 2w + -5x = 0 Solving 2w + -5x = 0 Move all terms containing w to the left, all other terms to the right. Add '5x' to each side of the equation. 2w + -5x + 5x = 0 + 5x Combine like terms: -5x + 5x = 0 2w + 0 = 0 + 5x 2w = 0 + 5x Remove the zero: 2w = 5x Divide each side by '2'. w = 2.5x Simplifying w = 2.5x

Subproblem 2

Set the factor '(5w + -8x)' equal to zero and attempt to solve: Simplifying 5w + -8x = 0 Solving 5w + -8x = 0 Move all terms containing w to the left, all other terms to the right. Add '8x' to each side of the equation. 5w + -8x + 8x = 0 + 8x Combine like terms: -8x + 8x = 0 5w + 0 = 0 + 8x 5w = 0 + 8x Remove the zero: 5w = 8x Divide each side by '5'. w = 1.6x Simplifying w = 1.6x

Solution

w = {2.5x, 1.6x}

See similar equations:

| 81-18y+y^2+y^2=53 | | 4z+2=8-4z | | r=(w-9)(w+9) | | 0=2x^2+15x+15 | | 3y+y=y+12 | | 2x-5x-20=-7+4x-8 | | 6.1a+14=81.1 | | f(x)=2x^3-10x+12x | | 3k-7/3=9 | | 6x-36+8=8x-8 | | x^2-6x+7=180 | | 0=2x^3-10x+12x | | 1a+14=81.1 | | 5x-7=-7x+26 | | X^2+10=10x-14 | | 9.6/1.1 | | 9(x-4)=-3x+84 | | 9-7k-(3k-3)= | | -4v-14=-9(v+1) | | 24=3/4n | | -7x+21=0 | | x^2-2x+3x+108=180 | | 5y-2y+-6=2-y | | 4x+8y=54 | | 70-6x=160-26x | | 20b^2-20b+1=0 | | -6x+3y=90 | | 14.375/4.16666666666667 | | 76-x=91-2x | | -3+3u=-21 | | 5x-3/4=9/4 | | V=two |

Equations solver categories